2016
DOI: 10.21608/jpp.2016.46138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Treatments on Improving Seed Multiplication Ratio in Potato by Stem Cutting

Abstract: A procedure for rapid multiplication technique of potato using stem cuttings induced to grow at the leaf nodes by removal the apical growing point is described. Sequential five experiments were conducted in the greenhouses and in the field of a private farm (Nubaria district, Bahaira Governorate, Egypt), during the period from 2012 to 2015. In the first experiment, the number of stem cuttings in the different tested cultivars ranged from 16.25 (cv. Patrones) to 38.50 (cv. Spunta). In the second experiment, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This implies that treating stem cuttings with IBA can not only increase the rooting percentage but also root initiation and the number of roots. Various research experiments have confirmed that the application of optimal hormone concentration is very important for the successful rooting of cuttings [25,26]. IBA treatment of stem cuttings may cause cambial activity that resulted in root induction and ultimately an increase in the number of roots per cutting.…”
Section: Root Numbermentioning
confidence: 99%
“…This implies that treating stem cuttings with IBA can not only increase the rooting percentage but also root initiation and the number of roots. Various research experiments have confirmed that the application of optimal hormone concentration is very important for the successful rooting of cuttings [25,26]. IBA treatment of stem cuttings may cause cambial activity that resulted in root induction and ultimately an increase in the number of roots per cutting.…”
Section: Root Numbermentioning
confidence: 99%
“…Seed multiplication factor refers to the ratio of seed yield after cleaning per hectare to the seed rate. Its association with seed yield and its improvement by seed treatment has been observed for chickpea (Xalxo et al., 2007) and potato (Ezzat, 2016), as well as by time of planting and fertilizer application for maize (Ibrahim, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Yasser et al ( 2018) reported that the application of 6000 ppm of IBA gave best growth and yield of potato. Ezzat (2016) reported that stem-cutting evaluation of seven potato cultivars showed signi cant variation among the cultivars, and the Spunta cultivar had the highest transplant survival, establishment, and tuber yield among the seven cultivars. Thus, the objective of the study was to assess the rooting of potato varieties for transplant survival, establishment, and tuber production at eld condition.…”
Section: Introductionmentioning
confidence: 99%